2017
DOI: 10.1038/ncomms13953
|View full text |Cite
|
Sign up to set email alerts
|

Mate choice in fruit flies is rational and adaptive

Abstract: According to rational choice theory, beneficial preferences should lead individuals to sort available options into linear, transitive hierarchies, although the extent to which non-human animals behave rationally is unclear. Here we demonstrate that mate choice in the fruit fly Drosophila melanogaster results in the linear sorting of a set of diverse isogenic female lines, unambiguously demonstrating the hallmark of rational behaviour, transitivity. These rational choices are associated with direct benefits, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 39 publications
0
45
1
Order By: Relevance
“…We filmed chambers from above using JVC Everio GZ‐HM440U video cameras on a time‐lapse setting (1 frame s −1 ) for ~4 hr. Videos files were analyzed using the program VideoFly (Arbuthnott, Fedina, Pletcher, & Promislow, ) (generously provided by of Dr. Scott Pletcher, University of Michigan) which was used to track the physical position of the individual females in each frame of the video. Using this software, we counted the number of frames that each female spent on the surface of each subchamber containing either a “high‐harm male,” “low‐harm male,” or were elsewhere in the chamber (Supplementary Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…We filmed chambers from above using JVC Everio GZ‐HM440U video cameras on a time‐lapse setting (1 frame s −1 ) for ~4 hr. Videos files were analyzed using the program VideoFly (Arbuthnott, Fedina, Pletcher, & Promislow, ) (generously provided by of Dr. Scott Pletcher, University of Michigan) which was used to track the physical position of the individual females in each frame of the video. Using this software, we counted the number of frames that each female spent on the surface of each subchamber containing either a “high‐harm male,” “low‐harm male,” or were elsewhere in the chamber (Supplementary Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies support the theory that the choice of mate in male flies is rational and adaptive (7)(8)(9). It has been demonstrated that male flies prefer to court young females, even decapitated ones, and that both gustatory and olfactory perception are involved in this mating preference; therefore, we expected that males would prefer to court well-fed females, as they also have better reproductive potential (10).…”
mentioning
confidence: 61%
“…Flies w 1118 , GMR-hid, ninaE 7 , orco 1 , ppk23-Gla4, ppk25-Gal4, UAS-hid, PromE (800)-Gal4, tubP-Gal80 ts , dilp [2,3,5]/TM3, foxo 21 , foxo w24 / TM6, OK72-Gal4, UAS-InR DN , and UAS-eloF-RNAi fly stocks were maintained on food that contained 5% sucrose, 5% yeast, 5% cornmeal food, 1% agar, and 0.23% Tegosept (Apex Bioresearch Products, San Diego, CA, USA). Yeast concentration was adjusted to 1, 5, or 20% as described in each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Dechaume‐Moncharmont, Freychet, Motreuil, and Cézilly () found that convict cichlid females were transitive in their preferences for males that varied in their size. Arbuthnott, Fedina, Pletcher, and Promislow () found that male mate choice for 10 isogenic lines of Drosophilia melanogaster was nearly perfectly transitive.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of rationality studies to date treat the population, not the individual, as the level of interest (for exceptions see Dechaume-Moncharmont et al, 2013;Shafir, 1994). For example, the Drosophilia study tested each male in a single binary test, not multiple tests, generating group-level preferences for each of the female lines instead of individual-level preferences (Arbuthnott et al, 2017). Gabel and Hennig (2016) tested female crickets multiple times for their mating preferences, but calculated population-level preferences.…”
mentioning
confidence: 99%